The Role of Intelligence in Addressing the Potential Threats of Identity Politics on Twitter Leading up to the 2024 Indonesian Election - Saronto, Saronto; Harahap, Ongku Sutan; Fernando, Yudha (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2023)
In our digital era, social media, particularly Twitter, has become a global phenomenon with 556 million monthly active users worldwide. In Indonesia, Twitter has 24 million active users and is ranked fifth globally. As Indonesia approaches the politically crucial year of 2024, marked by upcoming elections, the use of identity politics on platforms like Twitter poses a potential threat to the integrity of safe and democratic processes. This research aims to analyze the potential identity politics threats on Twitter social media leading up to the 2024 elections. The study also aims to analyze the role of intelligence in addressing potential identity politics threats on Twitter social media that may arise ahead of the 2024 elections. To address this concern, this research employs a qualitative approach, incorporating data collection techniques such as literature review, focus group discussions, and in-depth interviews with three key informants. The analysis is conducted through threat analysis methodologies. The central research question seeks to identify and understand the potential threats associated with identity politics on Twitter in the lead-up to the 2024 elections, and to delineate the role of intelligence agencies in countering these threats. The research findings have identified 12 potential threats related to identity politics on Twitter leading up to the 2024 elections, thereby offering actionable recommendations for intelligence agencies to consider in their efforts to safeguard the democratic process.